A self-repairable ramie fiber three-dimensional braided composite material and a preparation method thereof

By utilizing the self-healing mechanism of epoxy resin microcapsules and amine curing agent microcapsules in ramie fiber three-dimensional braided composite materials, the problems of interfacial debonding and microcracks in ramie fiber composite materials are solved, achieving multiple self-healing processes and stable recovery of material properties, making it suitable for aerospace, automotive and other fields.

CN122628490APending Publication Date: 2026-08-25SHANGHAI UNIV OF ENG SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610912658.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing technologies are unable to effectively solve the problems of interfacial debonding and microcracks in ramie fiber composites under load or environmental action, leading to a decline in material performance. Furthermore, the uneven dispersion of existing microcapsule self-healing systems in ramie fibers and the uneven dispersion of catalysts limit their application.

Method used

The composite material is composed of ramie fiber three-dimensional braided reinforcement and epoxy resin matrix. Epoxy resin microcapsules and amine curing agent microcapsules trigger rupture and mix and cure in the crack area to achieve self-healing function, avoiding dependence on catalyst. The microcapsules maintain high reactivity during the service life of the composite material.

Benefits of technology

It achieves repeated self-repair, improves the damage tolerance and service life of materials, and is suitable for structural components in aerospace, automotive and other fields, with high engineering application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122628490A_ABST
    Figure CN122628490A_ABST
Patent Text Reader

Abstract

The application provides a repeatable self-repairing ramie fiber three-dimensional braided composite material and a preparation method thereof, and belongs to the technical field of self-repairing composite materials.The repeatable self-repairing ramie fiber three-dimensional braided composite material provided by the application is composed of a ramie fiber three-dimensional braided reinforcing body and an epoxy resin matrix filled in the ramie fiber three-dimensional braided reinforcing body, and epoxy resin microcapsules and amine curing agent microcapsules are dispersed in the epoxy resin matrix;when a crack occurs in the self-repairing ramie fiber three-dimensional braided composite material, the epoxy resin microcapsules and the amine curing agent microcapsules in the crack area are triggered to break and release liquid core materials, and a mixed curing reaction is carried out in the crack area, so that the self-repairing function is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of self-healing technology of composite materials, and particularly relates to a repeatable self-healing ramie fiber three-dimensional braided composite material and its preparation method. Background Technology

[0002] Composite materials using natural fibers as reinforcement are gaining increasing attention in aerospace, automotive, and construction fields due to their advantages such as lightweight, high specific strength, renewability, and biodegradability. Among them, ramie fiber has high tensile strength and crystallinity, making it a high-performance natural fiber. However, the surface of ramie fiber contains a large number of polar groups, resulting in weak interfacial bonding when composited with a resin matrix. Under load or environmental influences, it is prone to interfacial debonding and microcracks, leading to a decline in material performance and limiting its engineering applications.

[0003] For the repair of microcracks in composite materials, existing technologies have developed exogenous self-healing systems based on microcapsules. These systems encapsulate the repair agent within microcapsules and disperse it within the matrix. When the crack propagates to the microcapsule, the capsule ruptures, releasing the repair agent and achieving automatic crack filling. However, existing microcapsule self-healing systems primarily target reinforcing composites made of synthetic fibers such as glass fiber and carbon fiber, with limited research on ramie fiber self-healing. Ramie fiber has high surface polarity and complex pores, making it difficult to achieve uniform dispersion of microcapsules when directly transplanted into synthetic fiber systems. Furthermore, the microcapsules are prone to premature rupture during the composite process, losing their self-healing function. In addition, most existing microcapsule self-healing systems rely on catalysts or latent curing agents, which generally suffer from uneven catalyst dispersion and insufficient compatibility with the resin system, leading to unstable repair effects and limiting their further application.

[0004] In view of the above, this application is hereby submitted. Summary of the Invention

[0005] This application provides a repeatable self-healing ramie fiber three-dimensional braided composite material and its preparation method, aiming to solve the above-mentioned problems or at least alleviate the defects existing in the prior art.

[0006] This application provides a repeatable self-healing ramie fiber three-dimensional braided composite material, which consists of a ramie fiber three-dimensional braided reinforcement and an epoxy resin matrix filled within the ramie fiber three-dimensional braided reinforcement. Epoxy resin microcapsules and amine curing agent microcapsules are dispersed in the epoxy resin matrix. When cracks occur in the self-healing ramie fiber three-dimensional braided composite material, the epoxy resin microcapsules and amine curing agent microcapsules in the crack area are triggered to rupture and release the liquid core material, which then mixes and cures in the crack area to achieve the self-healing function.

[0007] In some embodiments, the core material of the epoxy resin microcapsules is epoxy resin, including bisphenol A type epoxy resin; the core material of the amine curing agent microcapsules is an amine curing agent, including polyether amine curing agents; and the capsule walls of both the epoxy resin microcapsules and the amine curing agent microcapsules are urea-formaldehyde resin.

[0008] In some implementations, at least one of the following conditions is met: A. The particle size of epoxy resin microcapsules and / or amine curing agent microcapsules is 10μm~200μm, and can be selected as 50μm~100μm; B. The capsule wall thickness of epoxy resin microcapsules and / or amine curing agent microcapsules is 0.5μm to 5μm; C. The mass ratio of epoxy resin microcapsules to amine curing agent microcapsules is (1~3):1, and can be (1~2):1; D. The mass fraction of epoxy resin microcapsules and amine curing agent microcapsules in the epoxy resin matrix is ​​5wt%~25wt%, and can be selected as 8wt%~15wt%.

[0009] In some implementations, at least one of the following conditions is met: E. Ramie fiber three-dimensional braided reinforcement is made by three-dimensional braiding of ramie fiber as axial yarn and braiding yarn. The braiding yarn forms a braiding angle with respect to the axial direction of the ramie fiber three-dimensional braided reinforcement. The braiding angle is 15°~40°, and can be selected as 25°~35°. F. The linear density of ramie fiber is 2 × (180~220) tex; G. The fiber volume fraction of the repeatable self-healing ramie fiber three-dimensional braided composite material is 40%~60%, and can be selected as 45%~55%; H. The surface structure of the three-dimensional braided ramie fiber reinforcement is dense, while the internal structure is loose; I. In the direction from the outer surface of the ramie fiber three-dimensional braided reinforcement towards the inside, the braiding angle gradient of the ramie fiber three-dimensional braided reinforcement decreases; J. The weaving angle of the three-dimensional braided ramie fiber reinforcement decreases gradually within the range of 40° to 20° in the direction from the outer surface of the outer surface to the inner surface.

[0010] Another aspect of this application provides a method for preparing a repeatable self-healing ramie fiber three-dimensional braided composite material, which includes the following steps: Epoxy resin microcapsules and amine curing agent microcapsules were prepared separately. The matrix epoxy resin, matrix curing agent, epoxy resin microcapsules and amine curing agent microcapsules are mixed to obtain a mixture containing microcapsules; Ramie fibers are three-dimensionally woven into fiber preforms; A fiber preform was impregnated with a mixture containing microcapsules and then cured to obtain a repeatable self-healing ramie fiber three-dimensional braided composite material.

[0011] In some implementations, the fiber preform is woven using a four-step three-dimensional weaving process.

[0012] In some embodiments, impregnating the fiber preform with a microcapsule-containing mixture includes: injecting the microcapsule-containing mixture into the fiber preform under negative pressure using a vacuum-assisted resin transfer molding process.

[0013] In some implementations, the vacuum negative pressure during the infusion process is 0.06 MPa to 0.1 MPa, and the infusion time is controlled between 30 min and 60 min.

[0014] In some implementations, the vacuum negative pressure during the infusion process is 0.07 MPa to 0.1 MPa, and the infusion time is controlled at 50 min to 60 min.

[0015] In some embodiments, the curing process employs a staged heating curing method, comprising a first curing stage, a second curing stage, and a third curing stage performed sequentially; wherein, the first curing stage is maintained at a temperature range of 85℃ to 95℃ for 1.5 h to 2.5 h, the second curing stage is maintained at a temperature range of 115℃ to 125℃ for 0.5 h to 1.5 h, and the third curing stage is maintained at a temperature range of 145℃ to 155℃ for 3 h to 5 h.

[0016] In some implementations, the first curing stage is maintained at 88℃~92℃ for 1.8 h~2.2 h, the second curing stage is maintained at 118℃~122℃ for 0.8 h~1.2 h, and the third curing stage is maintained at 148℃~152℃ for 3.5 h~4.5 h.

[0017] In some embodiments, both epoxy resin microcapsules and amine curing agent microcapsules are prepared by in-situ polymerization. The in-situ polymerization method includes: using epoxy resin or amine curing agent as core material, adding the core material to a base liquid containing urea and formaldehyde and mixing it evenly, then adding emulsifier and dispersant to the base liquid containing the core material and stirring to form an emulsion containing core material droplets; adjusting the pH of the emulsion to alkaline to allow urea and formaldehyde to undergo a condensation reaction to generate urea-formaldehyde prepolymer; adjusting the pH of the emulsion to acidic to allow the urea-formaldehyde prepolymer to polymerize and deposit on the surface of the core material droplets to form a capsule wall, and obtaining epoxy resin microcapsules or amine curing agent microcapsules after post-treatment.

[0018] This application provides a repeatable self-healing ramie fiber three-dimensional braided composite material and its preparation method, which has at least the following beneficial effects: This application utilizes a composite material composed of a three-dimensional braided ramie fiber reinforcement and an epoxy resin matrix filled within it. Epoxy resin microcapsules and amine curing agent microcapsules are dispersed within the epoxy resin matrix. When cracks develop in the material, the epoxy resin and amine curing agent microcapsules in the crack area are triggered to rupture and release the liquid core material. A mixing and curing reaction occurs directly in the crack area without relying on any catalyst, thus avoiding problems such as uneven catalyst dispersion and poor compatibility with the resin system, ensuring the stability of the repair effect. Simultaneously, because both types of microcapsules are isolated and preserved by the capsule wall, microcapsules not penetrated by the crack can continue to release the repair agent in subsequent damage. Combined with the strong integrity, anti-delamination, and beneficial properties of the three-dimensional braided ramie fiber reinforcement, which facilitates the accumulation of repair agents, repeated self-repair after multiple damages can be achieved. Furthermore, the preparation method of the repeatable self-healing ramie fiber three-dimensional braided composite material involves preparing two types of microcapsules separately, mixing them with a matrix resin, impregnating the fiber preform, and then curing. The process is simple and reliable, effectively solving the problem of uniform dispersion of microcapsules and maintenance of structural integrity in the complex pores of natural fibers. This significantly improves the damage tolerance and service life of the material, making it suitable for structural components in aerospace, automotive, and other fields, and possessing high engineering application value.

[0019] Other features and advantages of the repeatable self-healing ramie fiber three-dimensional braided composite material and its preparation method provided in this application will be described in detail in the following specific embodiments. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0021] Figure 1 A schematic diagram of the structure of the repeatable self-healing ramie fiber three-dimensional braided composite material provided in the embodiments of this application; Figure 2 A schematic diagram illustrating the damage and microcapsule release mechanism of the repeatable self-healing ramie fiber three-dimensional braided composite material provided in this application embodiment; Figure 3 A schematic diagram illustrating the repair state of the repeatable self-healing ramie fiber three-dimensional braided composite material provided in the embodiments of this application; Figure 4 This is a schematic diagram of the structure of the repeatable self-healing ramie fiber three-dimensional braided composite material provided in the embodiments of this application, wherein the pore structure gradient of the ramie fiber three-dimensional braided reinforcement decreases in the direction from the outer surface of the outer surface of the ramie fiber three-dimensional braided reinforcement to the inner surface. Figure 5 This is a photograph of the fiber preform obtained during the preparation of the repeatable self-healing ramie fiber three-dimensional braided composite material in Example 1 of this application. Figure 6 The image shows a physical specimen of the repeatable self-healing ramie fiber three-dimensional braided composite material of Example 1 of this application. Figure 7 The figures are displacement-load curves of the repeatable self-healing ramie fiber three-dimensional braided composite material specimens of Example 1 of this application under different impact energies; where a) is the displacement-load curve of the specimen under 10J impact; b) is the displacement-load curve of the specimen under 15J impact; and c) is the displacement-load curve of the specimen under 20J impact. Figure 8 The images show a comparison of the damage morphology of specimens made of composite materials in Comparative Example 1 and Comparative Example 5 after impact. (a) shows the damage morphology of the specimen made of composite material in Comparative Example 1 after impact, and (b) shows the damage morphology of the specimen made of composite material in Comparative Example 5 after impact. Detailed Implementation

[0022] The following combination Figures 1 to 4 The specific embodiments of this application are described in detail. In the detailed description of the embodiments of this application, for ease of explanation, partial structures in the schematic diagrams may be enlarged beyond the general scale; that is, the schematic diagrams are not necessarily drawn to scale, and the schematic diagrams are merely examples, and should not limit the scope of protection of this application. The accompanying drawings show the preferred embodiments of this application. However, this application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to make the disclosure of this application more thorough and complete.

[0023] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0024] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0025] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0026] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0027] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0028] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0029] See Figure 1 , Figure 1 This is a schematic diagram of the structure of the repeatable self-healing ramie fiber three-dimensional braided composite material provided in this application embodiment. This application embodiment provides a repeatable self-healing ramie fiber three-dimensional braided composite material, consisting of a ramie fiber three-dimensional braided reinforcement 10 and an epoxy resin matrix filled within the ramie fiber three-dimensional braided reinforcement 10. Epoxy resin microcapsules 20 and amine curing agent microcapsules 30 are dispersed in the epoxy resin matrix. When cracks occur in the self-healing ramie fiber three-dimensional braided composite material, the epoxy resin microcapsules and amine curing agent microcapsules in the crack region 40 are triggered to rupture and release liquid core material. Subsequently, the two liquid core materials contact in the crack region 40 and undergo a mixed curing reaction, thereby automatically filling the crack and achieving a self-healing function.

[0030] Further reference Figure 2 and Figure 3 As shown, Figure 2 A schematic diagram illustrating the damage and microcapsule release mechanism of the repeatable self-healing ramie fiber three-dimensional braided composite material provided in this application embodiment; Figure 3 This is a schematic diagram of the repair state of the repeatable self-healing ramie fiber three-dimensional braided composite material provided in the embodiments of this application; when cracks occur in the self-healing ramie fiber three-dimensional braided composite material of this application embodiment, the epoxy resin microcapsules 20 and amine curing agent microcapsules 30 in the crack region 40 are triggered to rupture and release liquid core material for in-situ mixing and curing, filling the damage.

[0031] It should be understood that in the embodiments of this application, the core material mixed curing reaction released by the epoxy resin microcapsules 20 and the amine curing agent microcapsules 30 does not depend on a catalyst or latent curing agent, avoiding problems such as uneven catalyst dispersion, poor compatibility with the matrix, and easy deactivation during long-term storage, making the self-healing system simpler and more reliable. Based on this, both repair agents (epoxy resin and amine curing agent) are encapsulated and preserved within the capsule wall, maintaining fresh and highly reactive activity throughout the service life of the composite material, and will not cure prematurely due to contact with the matrix. Furthermore, since each crack propagation only consumes a portion of the microcapsules along the crack path, the reusable self-healing ramie fiber three-dimensional braided composite material still has a large number of intact microcapsules available for subsequent damage, thus achieving multiple repetitive self-healing. Simultaneously, the epoxy resin cures quickly and exhibits high bonding strength after direct contact with the amine curing agent, effectively restoring the mechanical properties of the material.

[0032] Furthermore, the ramie fiber three-dimensional braided reinforcement 10, as the skeleton of the repeatable self-healing ramie fiber three-dimensional braided composite material, not only bears the main mechanical load, but also provides continuous structural support for crack repair. When the crack propagates, the three-dimensional braided structure can constrain and guide the crack propagation path, avoid large-area delamination, and allow the repair agent to be effectively enriched in the crack area under capillary action, thereby improving the repair efficiency.

[0033] Therefore, the reusable self-healing ramie fiber three-dimensional braided composite material provided in this application can automatically repair cracks and restore most of its mechanical properties after the first damage. Furthermore, due to the restraining and guiding effect of the three-dimensional braided structure on crack propagation and the storage capacity of the microcapsules, the reusable self-healing ramie fiber three-dimensional braided composite material can still maintain a high repair rate after secondary damage. Simultaneously, since no catalyst is required, the repair effect is stable and reliable, unaffected by catalyst activity decay. Therefore, the reusable self-healing ramie fiber three-dimensional braided composite material provided in this application is suitable for structural components in aerospace, automotive, and other fields, possessing high damage tolerance and engineering application value.

[0034] It should be noted that the ramie fiber three-dimensional braided reinforcement in this application embodiment is made of ramie fiber. As a natural plant fiber, ramie fiber has a large number of hydroxyl groups on its surface, resulting in strong interfacial bonding with resin. At the same time, the fiber has good toughness and can effectively transfer crack stress, making it easier to trigger the release of repair agents from microcapsules during crack propagation. Moreover, compared with carbon fiber, ramie fiber has higher tensile strength and crystallinity, and the fiber body is less damaged after impact. This can endow the reusable self-healing ramie fiber three-dimensional braided composite material with good mechanical properties and structural integrity.

[0035] The "three-dimensional weaving" involved in the embodiments of this application refers to the weaving method of interlacing fibers in three spatial directions (warp, weft, and axial) to form an integral preform. In the embodiments of this application, the precursor of the ramie fiber three-dimensional weaving reinforcement, namely the fiber preform, is made by three-dimensional weaving process. Compared with the traditional two-dimensional lay-up or two-dimensional weaving structure, the three-dimensional weaving reinforcement has the advantages of strong integrity, high interlayer bonding force, and excellent anti-delamination performance.

[0036] In the embodiments of this application, the epoxy resin matrix refers to a continuous phase polymer material formed by curing epoxy resin as the main component. In the reusable self-healing ramie fiber three-dimensional braided composite material, the epoxy resin matrix fills the internal pores of the ramie fiber three-dimensional braided reinforcement, bonding the fiber reinforcement into a whole, while transferring and dispersing the load.

[0037] In this embodiment, a microcapsule refers to a tiny container formed by encapsulating a liquid repair agent, i.e., the core material, within a polymer capsule wall. In this embodiment, the core material of the epoxy resin microcapsule is liquid epoxy resin, and the core material of the amine curing agent microcapsule is a liquid amine curing agent; both have urea-formaldehyde resin capsule walls. The two types of microcapsules are uniformly dispersed in the epoxy resin matrix, isolated from each other, and remain stable under normal use conditions of the composite material. When a crack propagates to the microcapsule, stress concentration at the crack causes the capsule wall to rupture, releasing the core material. Since the epoxy resin and the amine curing agent can undergo a cross-linking and curing reaction at room temperature without any catalyst, the released liquid core materials mix in the crack area and then cure to form a cross-linked network, bonding the crack surface and achieving crack repair.

[0038] In some embodiments, the core material of the epoxy resin microcapsules is epoxy resin, specifically bisphenol A type epoxy resin, such as E-51 or E-54. Bisphenol A type epoxy resin has suitable viscosity and excellent mechanical properties after curing. The epoxy groups in its molecular structure react with amine curing agents to form a highly cross-linked network structure, which can form hydrogen bonds and chemical bonds with the polar groups on the surface of ramie fibers, thus achieving a stable bond between the epoxy resin matrix and the ramie fiber interface after crack repair.

[0039] In some embodiments, the core material of the amine curing agent microcapsules is an amine curing agent, specifically a polyether amine curing agent, such as polyether amine D230, D400, or T403. When the polyether amine curing agent reacts with the epoxy resin core material of the epoxy resin microcapsules, no catalyst is required, and the cured product exhibits high toughness and impact resistance. Compared to tertiary amine or imidazole catalysts, polyether amine curing agents do not contain metal ions or halogens, have better compatibility with the epoxy resin matrix, and exhibit excellent long-term storage stability, ensuring that the curing agent released during multiple repair processes maintains high reactivity.

[0040] In some embodiments, the capsule walls of both epoxy resin microcapsules and amine curing agent microcapsules are made of urea-formaldehyde resin. Urea-formaldehyde resin has high mechanical strength and good chemical corrosion resistance, which can effectively isolate the microcapsule core material from the external environment. At the same time, its Young's modulus is similar to that of the epoxy resin matrix, so that when cracks extend to the microcapsule, the capsule wall can rupture synchronously with the matrix without debonding or crack bypassing, thereby ensuring the timely release of the repair agent.

[0041] In some embodiments, the particle size of the epoxy resin microcapsules and / or amine curing agent microcapsules is 10 μm to 200 μm, optionally 50 μm to 100 μm; for example, the particle size of the epoxy resin microcapsules and / or amine curing agent microcapsules can be any particle size value within the range of 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm or 10 μm to 200 μm. When the microcapsule size is too large, it is difficult to disperse uniformly within the three-dimensional woven structure of the fiber preform, and large-sized microcapsules may become stress concentration points, affecting the mechanical properties of the composite material. When the particle size is too small, the total surface area of ​​the microcapsules increases, the proportion of the capsule wall material increases, the core material loading decreases, and excessively small microcapsules may not be effectively triggered to rupture during crack propagation. By controlling the microcapsule size between 10μm and 200μm, it can smoothly pass through the complex pore network of the three-dimensional woven ramie fiber preform, facilitating uniform dispersion, while also possessing sufficient core material loading and capsule wall mechanical strength. This allows the microcapsules to reliably rupture under the stress at the crack tip and release the repair agent, thereby improving the self-healing efficiency.

[0042] In some embodiments, the capsule wall thickness of the epoxy resin microcapsules and / or amine curing agent microcapsules is 0.5 μm to 5 μm; for example, the capsule wall thickness of the epoxy resin microcapsules and amine curing agent microcapsules can be any thickness value within the range of 0.5 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, or 0.5 μm to 5 μm. If the capsule wall is too thin, the microcapsules are prone to premature rupture during the composite material preparation process, resulting in premature release of the core material and participation in the curing of the epoxy resin matrix, thus losing the self-healing function; if the capsule wall is too thick, the capsule wall is difficult to rupture when cracks propagate, the core material cannot be released, and the self-healing function fails. By controlling the capsule wall thickness within the range of 0.5 μm to 5 μm, it is beneficial to the structural integrity of the microcapsules during processing, promoting their sensitive response to cracks during service.

[0043] In some embodiments, the mass ratio of epoxy resin microcapsules to amine curing agent microcapsules is (1~3):1, optionally (1~2):1; for example, the mass ratio of epoxy resin microcapsules to amine curing agent microcapsules can be any mass ratio within the range of 1:1, 1.25:1, 1.5:1, 1.75:1, 2:1, 2.25:1, 2.5:1, 2.75:1, 3:1, or (1~3):1. Maintaining a mass ratio within this range is beneficial for balancing the random distribution of the two types of microcapsules in the crack area and the mixing efficiency after release, promoting sufficient reaction and curing. If the epoxy resin ratio is too low, excessive curing agent may lead to brittleness and decreased bond strength in the repaired product; if the epoxy resin ratio is too high, incomplete curing and poor repair effect will result.

[0044] In some embodiments, the mass fraction of epoxy resin microcapsules and amine curing agent microcapsules in the epoxy resin matrix is ​​5wt% to 25wt%, optionally 8wt% to 15wt%. For example, the mass fraction of epoxy resin microcapsules and amine curing agent microcapsules in the epoxy resin matrix can be any mass fraction within the range of 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, or 5wt% to 25wt%. If the mass fraction of epoxy resin microcapsules and amine curing agent microcapsules in the epoxy resin matrix is ​​too low, the number of microcapsules available for repair per unit volume is insufficient, making it difficult to guarantee the need for repeated repairs, especially for large-area or multi-crack conditions where the repair effect is limited. If the mass fraction of epoxy resin microcapsules and amine curing agent microcapsules in the epoxy resin matrix is ​​too high, the proportion of particles in the system increases, which may adversely affect the continuity of the matrix and the fiber / matrix interface bonding, leading to a decrease in the initial mechanical properties of the material. At the same time, excessive microcapsules will occupy the volume of the epoxy resin matrix, reducing the mechanical properties of the reusable self-healing ramie fiber three-dimensional braided composite material. Controlling the mass fraction of epoxy resin microcapsules and amine curing agent microcapsules in the epoxy resin matrix within the range of 5wt% to 25wt% is beneficial for providing sufficient repair agent reserves to support multiple damage repair cycles and maintaining good bulk mechanical properties and uniform microcapsule dispersion of the composite material.

[0045] In some embodiments, the ramie fiber three-dimensional braided reinforcement is made by three-dimensionally braiding ramie fibers as axial yarns and braiding yarns. The braiding yarns form a braiding angle relative to the axial direction of the ramie fiber three-dimensional braided reinforcement, and the braiding angle is 15°~40°, optionally 25°~35°. For example, in the embodiments of this application, the braiding angle of the ramie fiber three-dimensional braided reinforcement can be any braiding angle value or range within the range of 15°, 16°, 17°, 18°, 19°, 20°, 21°, 22°, 23°, 24°, 25°, 26°, 27°, 28°, 29°, 30°, 31°, 32°, 33°, 34°, 35°, 36°, 37°, 38°, 39°, 40° or 15°~40°.

[0046] It should be understood that in a three-dimensional braided structure, the yarns involved in the braiding are divided into axial yarns and braiding yarns. In the precursor of the ramie fiber three-dimensional braided reinforcement in the embodiments of this application, i.e., in the fiber preform, the axial yarns extend along the axial direction (i.e., the length direction or the forming direction) of the fiber preform, while the braiding yarns interweave obliquely away from the axial direction and form a braiding angle relative to the axial direction. That is, the braiding angle refers to the angle between the direction of the braiding yarn and the axial direction of the fiber preform. The size of the braiding angle mainly affects the pore structure of the ramie fiber three-dimensional braided reinforcement. When the braiding angle is large, the yarn bundles are tightly interwoven, the porosity is low, and the structure is dense; when the braiding angle is small, the yarn bundles are relatively loose, and the structure has a higher porosity.

[0047] In this embodiment, the weaving angle of the ramie fiber three-dimensional braided reinforcement is 15°~40°. When the weaving angle is less than 15°, the ramie fiber yarns are excessively oriented along the axial direction, and the ramie fiber three-dimensional braided reinforcement exhibits anisotropy. During the preparation process, when microcapsules are filled into the fiber preform, channeling is easily generated along the fiber direction, resulting in uneven distribution. When the weaving angle is greater than 40°, the ramie fibers are too tightly interwoven, reducing the porosity of the fiber preform. The matrix resin precursor containing microcapsules is difficult to fully wet the interior of the fiber preform, and the microcapsules are easily filtered by the fiber bundles and retained on the surface. By controlling the weaving angle within the range of 15°~40°, it is beneficial to improve the overall mechanical properties of the composite material. The fiber preform has more suitable porosity and permeability, which promotes the full wetting of the matrix resin precursor containing microcapsules, and the microcapsules are evenly distributed in the epoxy resin matrix.

[0048] In some embodiments, the linear density of ramie fibers is 2 × (180~220) tex, optionally 2 × 197 tex. A linear density of 2 × (180~220) tex means that the ramie fibers are a double-strand yarn formed by twisting or paralleling two single yarns, with each single yarn having a linear density of 180~220 tex. It should be understood that if the linear density is too low, the fibers are too fine, making them prone to breakage during weaving, and the preform pores are too small, which is not conducive to the wetting of the matrix resin precursor and the dispersion of microcapsules. If the linear density is too high, the fibers are too coarse, the preform pores are too large, and the microcapsules are easily washed away and moved during infusion, resulting in uneven distribution.

[0049] In some embodiments, the fiber volume fraction of the reusable self-healing ramie fiber three-dimensional braided composite material is 40% to 60%, optionally 45% to 55%. For example, the fiber volume fraction of the reusable self-healing ramie fiber three-dimensional braided composite material can be any volume fraction value within the range of 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, or 45% to 55%. If the fiber volume fraction is below 40%, the reinforcement contributes insufficiently to the mechanical properties of the composite material. Simultaneously, if the matrix content is too high, the distance between microcapsules increases, and the repair effect may be affected due to insufficient microcapsule density along the crack propagation path. If the fiber volume fraction is above 60%, the reinforcement is too dense, making it difficult to impregnate the matrix resin precursor containing microcapsules. The microcapsules are easily filtered by the fibers and cannot be uniformly dispersed. Furthermore, if the matrix is ​​too thin, the microcapsules are easily exposed on the fiber surface and rupture prematurely during the preparation process.

[0050] It should be noted that while the epoxy resin microcapsules and amine curing agent microcapsules of this application can be uniformly distributed in the reusable self-healing ramie fiber three-dimensional braided composite material, this application does not pursue a theoretically absolute uniform distribution of microcapsules in the reusable self-healing ramie fiber three-dimensional braided composite material. In some embodiments, the flowing resin carrying the microcapsules is infused into the three-dimensional braided structure of the fiber preform. Due to the complex pore structure of the three-dimensional braided structure, the microcapsules can be filtered by the fiber bundles and retained in areas with larger voids, such as yarn bundle interlacing nodes, inter-yarn pores, and resin-rich areas. Therefore, the epoxy resin microcapsules and amine curing agent microcapsules in the embodiments of this application can be confined and distributed in the yarn bundle interlacing nodes, inter-yarn pores, and resin-rich areas within the reusable self-healing ramie fiber three-dimensional braided composite material. Since cracks preferentially propagate along yarn bundle interfaces, inter-yarn pores, and resin-rich areas when they are confined and distributed in these areas, they are more easily triggered. It is important to note that regions with a loose structure (such as those with a smaller weaving angle and higher porosity) have larger pore sizes, making it easier for microcapsules to enter and accumulate; while regions with a dense structure (such as those with a larger weaving angle and lower porosity) have smaller pore sizes, resulting in a relatively lower degree of microcapsule accumulation.

[0051] In the repeatable self-healing ramie fiber three-dimensional braided composite material provided in this application embodiment, the pore structure of the three-dimensional braided ramie fiber reinforcement can be uniformly distributed or gradient distributed in a certain direction. For example, refer to... Figure 1 and Figure 4 As shown, Figure 1 In the example of the repeatable self-healing ramie fiber three-dimensional braided composite material, the pore structure of the three-dimensional braided ramie fiber reinforcement 10 is uniformly distributed. Figure 4 This is a schematic diagram of the structure of the repeatable self-healing ramie fiber three-dimensional braided composite material provided in the embodiments of this application, wherein the outer surface 50 of the ramie fiber three-dimensional braided reinforcement 10 points inward, and the pore structure gradient of the ramie fiber three-dimensional braided reinforcement 10 decreases.

[0052] In the embodiments of this application, the uniform distribution of the pore structure of the three-dimensional braided ramie fiber reinforcement means that structural parameters such as braiding angle and yarn density remain basically consistent throughout the reinforcement, thereby obtaining a uniform pore structure. This structure is beneficial for simplifying the braiding process. The gradient distribution of the pore structure of the three-dimensional braided ramie fiber reinforcement in a certain direction means that its structural parameters (e.g., braiding angle) gradually change along a specific direction (e.g., from the outer surface to the interior), thus forming a gradient in the pore structure. Consequently, the degree of microcapsule enrichment also changes gradient along this direction. This gradient distribution design of the pore structure can actively guide the crack propagation path to a directional and concentrated propagation along a preset direction (e.g., from the outer surface to the interior), rather than random dispersion. This allows cracks to pass through the microcapsule-rich area more efficiently, significantly increasing the triggering probability of microcapsules, while avoiding excessive consumption of microcapsules due to large-area crack propagation at once, thereby supporting repeated self-repair.

[0053] Continue to refer to Figure 4 In some embodiments, the ramie fiber three-dimensional braided reinforcement 10 has a dense surface structure and a loose internal structure. It should be understood that the "surface" of the ramie fiber three-dimensional braided reinforcement 10 refers to the region near the outer surface 50 of the ramie fiber three-dimensional braided reinforcement, and correspondingly, the "interior" of the ramie fiber three-dimensional braided reinforcement refers to the core region away from the outer surface 50. The dense surface of the ramie fiber three-dimensional braided reinforcement 10 is relative to its interior. This dense surface and loose interior structure design can effectively guide cracks to propagate from the outer surface 50 to the interior when they are generated, preventing premature large-area extension of cracks on the outer surface 50. Simultaneously, the loose interior region has more pores and a higher concentration of microcapsules, making it easier for cracks to trigger microcapsules after entering the interior, thereby improving self-healing efficiency.

[0054] Continue to refer to Figure 4 In some embodiments, the weaving angle gradient of the ramie fiber three-dimensional braided reinforcement decreases in the inward direction of the outer surface 50. Because a larger weaving angle results in tighter yarn interweaving, a denser structure, lower porosity, and lower microcapsule enrichment, while a smaller weaving angle results in relatively looser yarns, higher porosity, and higher microcapsule enrichment, the reduced weaving angle gradient in the inward direction of the outer surface of the ramie fiber three-dimensional braided reinforcement creates a gradient change in pore structure. This achieves a gradient change from a dense surface to a loose interior, and from low microcapsule enrichment to high microcapsule enrichment, causing more microcapsules to be triggered sequentially as the crack propagates inward.

[0055] Continue to refer to Figure 4In some embodiments, the outer surface 50 of the ramie fiber three-dimensional braided reinforcement 10 points inward, and the braiding angle of the ramie fiber three-dimensional braided reinforcement 10 gradually decreases within the range of 40° to 20°. This not only helps the surface layer to have sufficient density to constrain cracks, but also provides appropriate loose channels and high-capsule enrichment areas inside, allowing cracks to smoothly enter the microcapsule enrichment area and be efficiently triggered. For example... Figure 4 As shown, the ramie fiber three-dimensional braided reinforcement can be divided into multiple layers in the direction pointing inward from the outer surface 50°, with the braiding angle of each layer gradually decreasing. For example, the first layer near the outer surface has a braiding angle of 40°, the second layer (the middle layer between the outer surface and the inner core layer) has a braiding angle of 35°, and the innermost core layer (the third layer) has a braiding angle of 30°. Those skilled in the art can select an appropriate number of layers and angle variation method according to the required gradient change rate and material performance requirements. In other embodiments, the ramie fiber three-dimensional braided reinforcement can be divided into multiple layers in the direction pointing inward from the outer surface based on different braiding angles, with the braiding angle difference between adjacent layers being 1°-5°. This small gradient change in braiding angle between adjacent layers can achieve a smooth transition of the pore structure, making it easier for cracks to propagate stably along the gradient direction and avoiding stress concentration or crack deflection caused by abrupt angle changes.

[0056] It should be noted that in the embodiments of this application, "the direction from the outer surface to the inside" refers to the thickness direction for flat fiber preforms, such as the direction perpendicular to the plate surface, and to the radial direction for columnar or tubular fiber preforms, that is, from the outer wall to the central axis or inner wall. The embodiments of this application all use columnar fiber preforms as an example for illustration, but those skilled in the art will understand that this gradient design is also applicable to other shapes of three-dimensional braided fiber preforms. Through the synergistic effect of the above gradient design and the confined distribution of microcapsules, the reusable self-healing ramie fiber three-dimensional braided composite material of this application can actively guide cracks to propagate along a preset path to the microcapsule-rich area, significantly increasing the triggering probability of microcapsules, while avoiding excessive consumption of microcapsules due to large-area crack propagation at once, thereby supporting multiple repetitive self-healing processes.

[0057] This application embodiment also provides a method for preparing a repeatable self-healing ramie fiber three-dimensional braided composite material, used to prepare the repeatable self-healing ramie fiber three-dimensional braided composite material as described above, including the following steps: Epoxy resin microcapsules and amine curing agent microcapsules were prepared separately. The matrix epoxy resin, matrix curing agent, epoxy resin microcapsules and amine curing agent microcapsules are mixed to obtain a mixture containing microcapsules; Ramie fibers are three-dimensionally woven into fiber preforms; A fiber preform was impregnated with a mixture containing microcapsules and then cured to obtain a repeatable self-healing ramie fiber three-dimensional braided composite material.

[0058] In the preparation method provided in this application embodiment, by preparing two types of microcapsules separately, the particle size, capsule wall thickness, and core material content of epoxy resin microcapsules and amine curing agent microcapsules can be independently controlled, ensuring that both maintain their integrity and reactivity during subsequent mixing and composite material molding. Further, the matrix epoxy resin, matrix curing agent, and the prepared epoxy resin microcapsules and amine curing agent microcapsules are mixed to obtain a mixture containing microcapsules. After the matrix epoxy resin and matrix curing agent are mixed, a curable resin system is formed, and the epoxy resin microcapsules and amine curing agent microcapsules are uniformly dispersed in the resin system. In this embodiment, ramie fibers are three-dimensionally woven into a fiber preform. The ramie fibers interweave in three spatial directions (warp, weft, and axial) to form a continuous spatial skeleton structure in the fiber preform, so that the fiber preform has high porosity and good integrity, providing conditions for the embedding of microcapsules and the flow of the resin to be cured. Finally, the fiber preform is impregnated with the above-mentioned mixture containing microcapsules, and then cured. The matrix epoxy resin and matrix curing agent are cured to form an epoxy resin matrix. The microcapsules are uniformly wrapped in the cured epoxy resin matrix, resulting in a repeatable self-healing ramie fiber three-dimensional woven composite material.

[0059] In some embodiments, the matrix epoxy resin and matrix curing agent can be ZTC-02AB (where ZTC-02A is the epoxy resin component and ZTC-02B is the curing agent component). The matrix epoxy resin can also be other optional bisphenol A type epoxy resins, such as E-51, DY-128, CYD-128, etc. Modified epoxy resins or low viscosity epoxy resins, such as E-44, can also be selected according to process requirements to replace or adjust the system performance.

[0060] In some embodiments, the fiber preform is woven using a four-step three-dimensional weaving process. This four-step process uses a Cartesian coordinate system to arrange the yarn carriers. The yarn carriers, acting as devices to control the movement of the fiber bundles, complete one motion cycle by moving sequentially in four steps along two orthogonal directions (rows and columns) on the weaving base. This achieves the interweaving of the fiber bundles in three spatial directions (warp, weft, and axial), forming a three-dimensional woven fiber preform. Specifically, the four-step process consists of four independent motion steps: First, the yarn carriers in odd-numbered rows move one step to the right, and the yarn carriers in even-numbered rows move one step to the left; second, the yarn carriers in odd-numbered columns move one step upward, and the yarn carriers in even-numbered columns move one step downward; third, the yarn carriers in odd-numbered rows move one step to the left, and the yarn carriers in even-numbered rows move one step to the right; fourth, the yarn carriers in odd-numbered columns move one step downward, and the yarn carriers in even-numbered columns move one step upward. After completing the above four steps, all yarn carriers return to their initial spatial layout, but the fiber bundles have already interwoven once in space, forming a weaving pitch. Repeating this cycle allows for the continuous weaving of the desired fiber preform length. Compared to traditional two-dimensional lay-up or two-dimensional weaving structures, the fiber preform produced by the four-step three-dimensional weaving process has advantages such as good integrity, strong interlayer bonding, and excellent anti-delamination performance. In reusable self-healing ramie fiber three-dimensional woven composite materials, this fiber preform acts as a skeleton, not only bearing the main mechanical load but also constraining the crack propagation path when cracks extend, preventing large-area delamination. This allows the liquid core material repair agent released from the microcapsules to effectively accumulate in the crack area under capillary action, thereby improving self-healing efficiency. During the weaving process, a fixed weaving angle, such as 25°, can be used to obtain a fiber preform with a uniform pore structure. Alternatively, the weaving angle can be changed layer by layer, altering the gradient. For example, the core layer, formed first, can be woven at a 25° angle, the middle layer near the core at a 30° angle, and the outermost layer adjacent to the middle layer at a 35° angle. The resulting fiber preform exhibits a decreasing gradient in pore structure from the outer surface to the interior. During weaving, the fiber volume fraction of the fiber preform can be controlled by adjusting the initial yarn arrangement or the degree of compaction.

[0061] In some embodiments, impregnating the fiber preform with a microcapsule-containing mixture includes: injecting the microcapsule-containing mixture into the fiber preform under negative pressure using a vacuum-assisted resin transfer molding (VARTM) process. The three-dimensionally woven ramie fiber preform has high porosity and high tortuosity, and its structure is complex. By employing the vacuum-assisted resin transfer molding (VARTM) process, the microcapsule-containing mixture is pressed into the fiber preform under negative pressure, which effectively reduces injection resistance and facilitates uniform dispersion of the microcapsule-containing mixture within the pores of the fiber preform, while simultaneously avoiding damage to the microcapsules due to excessive injection pressure.

[0062] In some embodiments, the vacuum negative pressure during the infusion process is 0.06 MPa to 0.1 MPa, and the infusion time is controlled between 30 min and 60 min. When the vacuum negative pressure is below 0.06 MPa, the driving force is insufficient, and the mixture containing microcapsules cannot fully wet the internal pores of the fiber preform, which easily leads to dry spots or uneven distribution of microcapsules. When the vacuum negative pressure is above 0.1 MPa, the pressure difference on the microcapsule walls is too large, which easily causes premature rupture during the infusion process. When the infusion time is less than 30 min, the flow rate is too fast, and the microcapsules are easily ruptured by strong shear forces, and the resin flow front is unstable, which may form bubble defects. When the infusion time is more than 60 min, the matrix epoxy resin may begin to gel during the infusion process, increasing the infusion resistance and hindering the uniform distribution of microcapsules. By controlling the vacuum negative pressure during the infusion process to 0.06 MPa ~ 0.1 MPa and the infusion time to 30 min ~ 60 min, the matrix resin can be fully impregnated with the fiber preform, minimizing bubble defects and inhibiting the structural damage of microcapsules under negative pressure.

[0063] In some embodiments, the vacuum negative pressure during the infusion process is 0.07 MPa to 0.1 MPa, and the infusion time is controlled at 50 min to 60 min, so as to promote the matrix resin to fully impregnate the fiber preform and minimize bubble defects, while avoiding structural damage to the microcapsules under negative pressure.

[0064] In some embodiments, the curing process employs staged temperature-increase curing, including a first curing stage, a second curing stage, and a third curing stage performed sequentially. Specifically, the first curing stage is maintained at a temperature range of 85℃ to 95℃ for 1.5 to 2.5 hours; the second curing stage is maintained at a temperature range of 115℃ to 125℃ for 0.5 to 1.5 hours; and the third curing stage is maintained at a temperature range of 145℃ to 155℃ for 3 to 5 hours. Staged temperature-increase curing avoids the microcapsules from bursting due to rapid expansion of the internal core material caused by rapid heating, while also promoting the gradual cross-linking of the epoxy resin matrix and reducing internal stress. The first curing stage involves pre-curing at 85℃~95℃ for 1.5h~2.5h to allow the resin system to initially gel, during which the microcapsules remain stable. The second curing stage involves curing at 115℃~125℃ for 0.5h~1.5h to promote further cross-linking of the resin and moderately harden the microcapsule walls. The third curing stage involves curing at 145℃~155℃ for 3h~5h to ensure complete cross-linking of the resin, resulting in excellent mechanical properties. By designing the temperature and holding time of each curing stage within the above range, the microcapsule wall structure can be modified while the matrix epoxy resin is cured under the action of the matrix curing agent, thus improving the microcapsule's high burst response characteristics during service.

[0065] In some embodiments, the first curing stage is maintained at 88℃~92℃ for 1.8 h~2.2 h, the second curing stage is maintained at 118℃~122℃ for 0.8 h~1.2 h, and the third curing stage is maintained at 148℃~152℃ for 3.5 h~4.5 h. The temperature and holding time of each curing stage are designed within the above ranges to ensure that the matrix resin achieves optimal curing while maximally protecting the microcapsule wall structure and ensuring that the microcapsules exhibit sensitive rupture response characteristics during service.

[0066] It should be understood that, based on the knowledge of the particle size, capsule wall size and material composition of the epoxy resin microcapsules and amine curing agent microcapsules in the embodiments of this application, those skilled in the art can use common microcapsule preparation methods such as in-situ polymerization, interfacial polymerization, coagulation, solvent evaporation, spray drying, fluidized bed coating, and phase separation to prepare epoxy resin microcapsules and amine curing agent microcapsules.

[0067] In some embodiments of this application, both epoxy resin microcapsules and amine curing agent microcapsules are prepared by in-situ polymerization. The in-situ polymerization method includes: using epoxy resin or amine curing agent as core material, adding the core material to a base liquid containing urea and formaldehyde and mixing it evenly, then adding emulsifier and dispersant to the base liquid containing the core material and stirring to form an emulsion containing core material droplets; adjusting the pH of the emulsion to alkaline to allow urea and formaldehyde to undergo condensation reaction to generate urea-formaldehyde prepolymer; adjusting the pH of the emulsion to acidic to allow the urea-formaldehyde prepolymer to polymerize and deposit on the surface of the core material droplets to form a capsule wall, and obtaining epoxy resin microcapsules or amine curing agent microcapsules after post-treatment.

[0068] Specifically, taking the in-situ polymerization of epoxy resin microcapsules as an example, bisphenol A type epoxy resin is used as the core material. The bisphenol A type epoxy resin is added to a reaction system containing urea, formaldehyde aqueous solution, and deionized water, and stirred and mixed uniformly at room temperature. Deionized water serves as the reaction medium to provide a uniform dispersion environment and control the system concentration. The mass ratio of urea to formaldehyde is 1:2 to 1:3, and the amount of deionized water added is 3 to 8 times the total mass of the urea and formaldehyde solution. The mass ratio of the core material to the reaction system is 1:2 to 1:4. Subsequently, emulsifier OP-10 and dispersant sodium dodecyl sulfate are added to the mixture. High-speed shear emulsification forms an emulsion containing core material droplets. The emulsifier reduces interfacial tension and promotes the dispersion of the oil phase to form a stable emulsion, while the dispersant prevents droplet aggregation and improves system stability. The amount of emulsifier is 0.5% to 1.5% of the total mass of the emulsion system, and the amount of dispersant is 0.1% to 0.5% of the total mass of the emulsion system. After emulsion formation, the pH of the system is adjusted to 8.0–9.0, and the reaction is carried out at 60℃–75℃ for 1–3 hours to allow urea and formaldehyde to undergo a condensation reaction to generate urea-formaldehyde prepolymer. Subsequently, the pH is adjusted to 3.0–3.5, and the reaction is continued at 60℃–70℃ for 3–5 hours to allow urea-formaldehyde resin to deposit on the surface of the emulsion droplets to form capsule walls. After the reaction is completed, epoxy resin microcapsules are obtained after post-treatment such as cooling, separation, washing, and drying. Washing is used to remove unreacted monomers and impurities, and drying is used to obtain stable powdered microcapsules. The in-situ polymerization method for preparing amine curing agent microcapsules differs from that for epoxy resin microcapsules only in the core material; the other raw materials and process parameters are the same and will not be described further here.

[0069] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all reagents and raw materials used in the embodiments are commercially available or synthesized by conventional methods, and the instruments used in the embodiments are also commercially available.

[0070] Example 1 This embodiment provides a repeatable self-healing ramie fiber three-dimensional braided composite material, the preparation process of which includes: (I) Microcapsule preparation Epoxy Resin Microcapsules: Urea and a 37% formaldehyde solution were mixed at a mass ratio of 1:2, and deionized water was added to prepare the base solution. The amount of deionized water was 5 times the total mass of the urea and formaldehyde solution. Bisphenol A type epoxy resin E-51 was added to the base solution and mixed evenly. Then, emulsifier OP-10 and dispersant sodium dodecyl sulfate were added and stirred at high speed to form a stable emulsion containing core material droplets. The amount of emulsifier was 1.2% of the total mass of the emulsion system, and the amount of dispersant was 0.4% of the total mass of the emulsion system. The stirring speed was 10,000 rpm, and the stirring time was 10 min. After the emulsion was formed, the pH of the emulsion was adjusted to 8.5 with triethanolamine, and the temperature was raised to 70℃ for 1.5 h. At this time, urea and formaldehyde underwent a condensation reaction to generate urea-formaldehyde prepolymer. The pH of the emulsion was then adjusted to 3.0 with dilute hydrochloric acid, and the temperature was further increased to 60°C with stirring for 4 hours to allow the urea-formaldehyde prepolymer to polymerize and deposit on the surface of the core material droplets, forming the capsule wall. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the product was washed successively with deionized water and acetone. It was then dried in a vacuum drying oven at 50°C for 2 hours to obtain epoxy resin microcapsules.

[0071] Amine curing agent microcapsules: The preparation method is the same as that of epoxy resin microcapsules, except that the core material is replaced with a polyether amine curing agent (polyether amine D230).

[0072] The average particle size of the obtained epoxy resin microcapsules and amine curing agent microcapsules was 75 μm, and the capsule wall thickness was 2 μm.

[0073] (ii) Preparation of mixtures containing microcapsules Take epoxy composite material ZTC-02AB as the matrix epoxy resin, in which ZTC-02A (epoxy resin component) 216g and ZTC-02B (curing agent component) 184g are thoroughly mixed according to the mass ratio. Then, add 20g of epoxy resin microcapsules and 20g of amine curing agent microcapsules to the mixture, with the mass ratio of epoxy resin microcapsules to amine curing agent microcapsules being 1:1. Stir at a low speed of 300rpm for 20min to uniformly disperse the two types of microcapsules, thus obtaining a mixture containing microcapsules.

[0074] (III) Preparation of fiber preforms The four-step three-dimensional weaving process is adopted, using ramie fiber (PR5258, 2×197tex) as raw material, setting the weaving angle to 30°, and weaving it into a columnar fiber preform. The fiber volume fraction is controlled at 50%, and the fiber preform has a uniform pore structure.

[0075] (iv) Molding of repeatable self-healing ramie fiber three-dimensional braided composite material The fiber preform was placed in a mold, and the mold was evacuated to a negative pressure of 0.08 MPa. The mixture containing microcapsules was injected into the mold over a time of 55 minutes. After the mixture completely impregnated the fiber preform, the preform was cured in stages according to the following procedure: the temperature was increased to 90°C at a rate of 2°C / min and held for 2 hours; then increased to 120°C at a rate of 2°C / min and held for 1 hour; finally, the temperature was increased to 150°C at a rate of 2°C / min and held for 4 hours. After naturally cooling to room temperature, the preform was demolded to obtain a repeatable self-healing ramie fiber three-dimensional braided composite material. In the repeatable self-healing ramie fiber three-dimensional braided composite material, the fiber volume fraction was 50%, and the mass fraction of epoxy resin microcapsules and amine curing agent microcapsules in the epoxy resin matrix was 10 wt%.

[0076] Example 2 The only difference from Example 1 is that, in the preparation of the microcapsule-containing mixture, the amount of epoxy resin microcapsules and amine curing agent microcapsules added is 50g each, and in the preparation of the fiber preform, the fiber volume fraction is controlled at 45%. In the obtained reusable self-healing ramie fiber three-dimensional braided composite material, the mass fraction of epoxy resin microcapsules and amine curing agent microcapsules in the epoxy resin matrix is ​​25wt%.

[0077] Example 3 The only difference from Example 1 is that, in the preparation of the microcapsule-containing mixture, the amount of epoxy resin microcapsules and amine curing agent microcapsules added is 60g each, and in the preparation of the fiber preform, the fiber volume fraction is controlled at 55%. In the obtained reusable self-healing ramie fiber three-dimensional braided composite material, the mass fraction of epoxy resin microcapsules and amine curing agent microcapsules in the epoxy resin matrix is ​​30wt%.

[0078] Example 4 The only difference from Example 1 is that the weaving angle during the fiber preform preparation process is set to 15°.

[0079] Example 5 The only difference from Example 1 is that the weaving angle during the fiber preform preparation process is set to 45°.

[0080] Example 6 The only difference from Example 1 is that the fiber preform preparation steps are different. Specifically, the weaving angle is set to decrease in a layered gradient within the range of 40°-20° in the direction from the outer surface to the inside of the fiber preform, and the weaving angle between two adjacent layers differs by 5° to form a fiber preform.

[0081] Example 7 The only difference from Example 1 is that the fiber preform preparation steps are different. Specifically, the weaving angle is set to decrease in a layered gradient within the range of 40°-20° in the direction from the outer surface to the inside of the fiber preform, and the weaving angle between two adjacent layers differs by 10° to form a fiber preform.

[0082] Example 8 The only difference from Example 1 is that, in the preparation of the mixture containing microcapsules, the amount of epoxy resin microcapsules added is 30g, the amount of amine curing agent microcapsules added is 10g, and the mass ratio of epoxy resin microcapsules to amine curing agent microcapsules is 3:1.

[0083] Example 9 The only difference from Example 1 is that: in the preparation of the mixture containing microcapsules, the amount of epoxy resin microcapsules added is 32g, the amount of amine curing agent microcapsules added is 8g, and the mass ratio of epoxy resin microcapsules to amine curing agent microcapsules is 4:1; in the preparation of the fiber preform, the fiber volume fraction is controlled at 55%.

[0084] Example 10 The only difference from Example 1 is the microcapsule preparation process, specifically: (I) Microcapsule preparation Epoxy Resin Microcapsules: Urea and a 37% formaldehyde solution were mixed at a mass ratio of 1:2.5, and deionized water was added to prepare the base solution. The amount of deionized water was 5 times the total mass of the urea and formaldehyde solution. Bisphenol A type epoxy resin E-51 as the core material was added to the base solution and mixed evenly. Then, emulsifier OP-10 and dispersant sodium dodecyl sulfate were added and stirred at high speed to form a stable emulsion containing core material droplets. The amount of emulsifier was 1.2% of the total mass of the emulsion system, and the amount of dispersant was 0.4% of the total mass of the emulsion system. The stirring speed was 6000 rpm and the stirring time was 15 min. After the emulsion was formed, the pH of the emulsion was adjusted to 8.5 with triethanolamine, and the temperature was raised to 70℃ for 2 h. At this time, urea and formaldehyde underwent a condensation reaction to generate urea-formaldehyde prepolymer. The pH of the emulsion was then adjusted to 3.0 with dilute hydrochloric acid, and the temperature was further adjusted to 60°C with stirring for 6 hours to allow the urea-formaldehyde prepolymer to polymerize and deposit on the surface of the core material droplets, forming the capsule wall. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the product was washed successively with deionized water and acetone. It was then dried in a vacuum drying oven at 50°C for 2 hours to obtain epoxy resin microcapsules.

[0085] Amine curing agent microcapsules: The preparation method is the same as that of epoxy resin microcapsules, except that the core material is replaced with a polyether amine curing agent (polyether amine D230).

[0086] The average particle size of both epoxy resin microcapsules and amine curing agent microcapsules is 120 μm, and the capsule wall thickness is 7 μm.

[0087] (III) Preparation of fiber preforms During the preparation of the fiber preform, the fiber volume fraction is controlled at 55%.

[0088] Example 11 The only difference from Example 1 is the microcapsule preparation process, specifically: (I) Microcapsule preparation Epoxy Resin Microcapsules: Urea and a 37% formaldehyde solution were mixed at a mass ratio of 1:3, and deionized water was added to prepare the base solution. The amount of deionized water was 5 times the total mass of the urea and formaldehyde solution. Bisphenol A type epoxy resin E-51 (core material) was added to the base solution and mixed thoroughly. Then, emulsifier OP-10 and dispersant sodium dodecyl sulfate were added, and the mixture was stirred and sheared at high speed to form a stable emulsion containing core material droplets. The amount of emulsifier was 1.2% of the total mass of the emulsion system, and the amount of dispersant was 0.4% of the total mass of the emulsion system. The stirring speed was 5000 rpm, and the stirring time was 20 min. After the emulsion was formed, the pH of the emulsion was adjusted to 8.5 with triethanolamine, and the temperature was raised to 75℃ for 2 h. At this time, urea and formaldehyde underwent a condensation reaction to generate urea-formaldehyde prepolymer. Then, the pH of the emulsion was adjusted to 3.0 with dilute hydrochloric acid, and the temperature was further adjusted to 60℃ and stirred for 2 h, allowing the urea-formaldehyde prepolymer to polymerize and deposit on the surface of the core material droplets to form the capsule wall. After the reaction was completed, the product was cooled to room temperature, filtered, washed with deionized water and acetone in sequence, and dried in a vacuum drying oven at 50°C for 2 hours to obtain epoxy resin microcapsules.

[0089] Amine curing agent microcapsules: The preparation method is the same as that of epoxy resin microcapsules, except that the core material is replaced with a polyether amine curing agent (polyether amine D230).

[0090] The average particle size of both epoxy resin microcapsules and amine curing agent microcapsules is 300 μm, and the capsule wall thickness is 5 μm.

[0091] Example 12 The only difference from Example 1 is that the vacuum negative pressure is 0.06 MPa and the infusion time is controlled at 40 min.

[0092] Example 13 The only difference from Example 1 is that the vacuum negative pressure is 0.12 MPa and the infusion time is controlled at 20 min.

[0093] Comparative Example 1 The only difference from Example 1 is that epoxy resin microcapsules and amine curing agent microcapsules are not added.

[0094] Comparative Example 2 The only difference from Example 1 is that the mixture containing microcapsules is prepared by adding only epoxy resin microcapsules and adding a latent curing agent (8g of dicyandiamide, accounting for 2wt% of the matrix resin mixture) as a catalyst to the matrix resin mixture. The amount of epoxy resin microcapsules added is 40g, accounting for 10wt% of the matrix resin mixture.

[0095] Comparative Example 3 The only difference from Example 1 is that a two-dimensional layered structure is used instead of a three-dimensional woven preform. The layering scheme is [0 / 90]4 layers, and the fiber volume fraction is still controlled at 50%, using ramie fibers of the same specification. In the specific preparation process, the ramie fibers are first laid flat on the mold in the 0° direction, keeping the fibers parallel and evenly tensioned to ensure consistent spacing between fibers. Then, a fiber layer in the 90° direction is laid on top, so that the two layers of fibers are perpendicular to each other and maintain a uniform spacing to avoid fiber entanglement or folding. Subsequently, the fibers in the 0° and 90° directions are laid in sequence until a complete four-layer [0 / 90]4 layered structure is formed.

[0096] Comparative Example 4 The only difference from Example 1 is that ramie fiber is replaced with flax fiber, and the type and linear density of flax fiber are similar to those of ramie fiber.

[0097] Comparative Example 5 The difference from Comparative Example 1 is that ramie fibers were replaced with carbon fibers.

[0098] It should be noted that in the above embodiments and comparative examples, the fiber preforms prepared are all columnar, for example... Figure 5 In Example 1, the four-step three-dimensional weaving process is used to weave a columnar fiber preform, the length direction of which is the axial direction, which is also the forming direction during the weaving process.

[0099] Furthermore, in the above examples and comparative examples, the ramie fiber was sourced from Hunan Huasheng Dongting Hemp Industry Co., Ltd. (PR5258), and the linear density of the ramie fiber was 2×197 tex. Flax fiber was purchased from Muling Jintaiheng Flax Textile Co., Ltd. Carbon fiber was purchased from Zhongfu Shenying Carbon Fiber Co., Ltd. (T700-12k). Urea was sourced from Sinopharm Chemical Reagent Co., Ltd., formaldehyde from Sinopharm Chemical Reagent Co., Ltd., bisphenol A epoxy resin E-51 from Suzhou Wodawei Materials Technology Co., Ltd., emulsifier OP-10 from Sinopharm Chemical Reagent Co., Ltd., dispersant sodium dodecyl sulfate from Sinopharm Chemical Reagent Co., Ltd., polyetheramine D230 from Guangdong Dahua New Materials Co., Ltd., and epoxy resin compound ZTC-02AB from Suzhou Wodawei Materials Technology Co., Ltd.

[0100] Physicochemical analysis The parameters of the repeatable self-healing ramie fiber three-dimensional braided composite materials prepared in each embodiment and comparative example are statistically analyzed and shown in Tables 1 and 2 below.

[0101] Table 1. Statistical table of parameter data for repeatable self-healing ramie fiber three-dimensional braided composite materials.

[0102] Table 2. Statistical table of parameter data for repeatable self-healing ramie fiber three-dimensional braided composite materials.

[0103] The performance of the repeatable self-healing ramie fiber three-dimensional braided composite materials prepared in each embodiment and comparative example was tested. The test methods included: Specimen Preparation: The columnar composite materials prepared in the above embodiments and comparative examples were radially cut into multiple block specimens of the same size. After cutting, the surface of the specimens was sanded with sandpaper to remove burrs and ensure uniform specimen dimensions. (Refer to the specimen obtained by cutting the composite material prepared in Example 1.) Figure 6 As shown.

[0104] Impact Test: A drop hammer impact testing machine was used. During the test, the specimen was placed at the center of the support platform of the impact testing machine, with the original outer surface of the specimen (excluding the cut surface) as the impact surface (the impact force was applied perpendicular to this outer surface). The impact energy was adjusted to 10J by adjusting the drop hammer height, and the specimen was subjected to the first impact load. The load-displacement curve during the impact process was recorded in real time by the data acquisition system. Subsequently, the specimen was placed in a constant temperature oven for heat treatment at 80 ℃ for 2 hours to promote the reaction of the repair agent and complete the crack repair. After the repair was completed, the specimen was removed and cooled to room temperature. After the specimen cooled, a second 10J impact test was performed, and the load-displacement response curve during the impact process was recorded again. The specimen was then placed in an 80℃ oven for 2 hours for a second repair treatment. After the specimen cooled to room temperature, a third 10J impact test was performed, and the impact load-displacement curve was recorded.

[0105] Adjust the impact energy conditions by adjusting the drop hammer height to achieve impact energies of 15J and 20J, and repeat the above test operation. Example 1: Displacement-load curves of composite material specimens under different impact energies (reference). Figure 7 As shown.

[0106] The peak loads of specimens under different impact energy conditions were statistically analyzed, and their repair rate was calculated. The repair rate (%) = (peak impact load after repair / peak impact load of the first impact) × 100%. The statistical results of the test are shown in Table 3 below.

[0107] Table 3. Statistical table of self-healing performance parameters of specimens under different impact energies.

[0108]

[0109] Performance Analysis: Combined with Table 1-3 and Figure 7-8 As can be seen, compared with Comparative Examples 1-5, the repeatable self-healing ramie fiber three-dimensional braided composite materials in Examples 1-13 consist of ramie fiber three-dimensional braided reinforcement and an epoxy resin matrix filled within the ramie fiber three-dimensional braided reinforcement. Epoxy resin microcapsules and amine curing agent microcapsules are uniformly dispersed in the epoxy resin matrix. After undergoing repeated "impact-repair-re-impact" processes, its peak load exhibits a changing pattern of "highest on the first impact, some recovery after repair, and maintaining a certain load-bearing capacity after the second repair." With increasing impact energy, the degree of material damage intensifies, and the peak load gradually decreases. However, the repaired specimen can still recover some mechanical properties, indicating that the system has good repeatable self-healing ability.

[0110] Specifically, compared to Example 1, Comparative Example 1 does not contain epoxy resin microcapsules or amine curing agent microcapsules. After the first repair, the peak impact load is significantly reduced, indicating that Comparative Example 1 essentially lacks self-healing ability. Compared to Example 1, Comparative Example 2 does not contain amine curing agent microcapsules; instead, it uses a latent curing agent added to the matrix resin mixture as a catalyst. Its second repair rate is significantly lower than that of Example 1, demonstrating the significant advantage of the catalyst-free two-component microcapsule system in multiple repairs. Compared to Example 1, Comparative Example 3 does not have a three-dimensional braided structure, and its second repair rate is much lower than that of Example 1, verifying that the constraint and guidance effect of the three-dimensional braided structure on cracks helps achieve repeatable self-healing. Compared with Example 1, Comparative Example 4 uses flax fiber as the weaving yarn. The surface of flax fiber has more wax and non-cellulose components, resulting in weaker interfacial bonding and easier local aggregation of fibers. The crack paths are more concentrated, leading to a decrease in the microcapsule triggering rate and thus a lower repair efficiency. The second repair rate of Comparative Example 4 is significantly lower than that of Example 1, proving that ramie fiber, due to its special microstructure and damage buffering properties, is more suitable for the repeatable self-healing system of this application.

[0111] It is worth noting that the damage morphology of the specimens in Comparative Example 1 and Comparative Example 5 after impact is compared to that of the specimens in Comparative Example 5. Figure 8As shown, the damage to the ramie fiber composite material in Comparative Example 1 was mainly concentrated in the resin matrix, with less damage to the fiber itself, and the overall structure still maintained a certain degree of integrity. In contrast, the carbon fiber composite material in Comparative Example 5 not only experienced resin matrix cracking under impact, but also exhibited significant fiber breakage and interlaminar separation. This difference indicates that ramie fiber composite materials possess a certain degree of damage buffering capacity under impact, which is beneficial for maintaining structural continuity and provides a basis for the self-healing process.

[0112] The technical features described above can be combined arbitrarily. Although not all possible combinations of these technical features are described, any combination of these technical features should be considered to be covered by this specification, provided that such combination does not contain contradictions.

[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A repeatable self-healing ramie fiber three-dimensional woven composite material, characterized in that, It is composed of a three-dimensional braided ramie fiber reinforcement and an epoxy resin matrix filled in the three-dimensional braided ramie fiber reinforcement, wherein epoxy resin microcapsules and amine curing agent microcapsules are dispersed in the epoxy resin matrix; When cracks occur in the self-healing ramie fiber three-dimensional braided composite material, the epoxy resin microcapsules and amine curing agent microcapsules in the cracked area are triggered to rupture and release the liquid core material, which then mixes and cures in the cracked area.

2. The repeatable self-healing ramie fiber three-dimensional woven composite material according to claim 1, characterized in that, The core material of the epoxy resin microcapsules is epoxy resin, including bisphenol A type epoxy resin; The core material of the amine curing agent microcapsules is an amine curing agent, including polyether amine curing agents; The capsule walls of both the epoxy resin microcapsules and the amine curing agent microcapsules are made of urea-formaldehyde resin.

3. The repeatable self-healing ramie fiber three-dimensional woven composite material according to claim 1 or 2, characterized in that, At least one of the following conditions must be met: A. The particle size of the epoxy resin microcapsules and / or the amine curing agent microcapsules is 10μm~200μm; B. The capsule wall thickness of the epoxy resin microcapsules and / or the amine curing agent microcapsules is 0.5 μm to 5 μm; C. The mass ratio of the epoxy resin microcapsules to the amine curing agent microcapsules is (1~3):1; D. The mass fraction of the epoxy resin microcapsules and the amine curing agent microcapsules in the epoxy resin matrix is ​​5wt%~25wt%.

4. The repeatable self-healing ramie fiber three-dimensional woven composite material according to claim 1 or 2, characterized in that, At least one of the following conditions must be met: E. The ramie fiber three-dimensional braided reinforcement is made by three-dimensionally braiding ramie fiber as axial yarn and braiding yarn. The braiding yarn forms a braiding angle with respect to the axial direction of the ramie fiber three-dimensional braided reinforcement. The braiding angle is 15°~40°. F. The linear density of the ramie fiber is 2 × (180~220) tex; G. The fiber volume fraction of the reusable self-healing ramie fiber three-dimensional braided composite material is 40%~60%; H. The surface structure of the three-dimensional braided ramie fiber reinforcement is dense, while the internal structure is loose; I. The weaving angle gradient of the three-dimensional braided ramie fiber reinforcement decreases in the direction from the outer surface of the outer surface towards the interior. J. The braiding angle of the three-dimensional braided ramie fiber reinforcement decreases gradually within the range of 40° to 20° in the direction from the outer surface of the outer surface of the ramie fiber three-dimensional braided reinforcement towards the inside.

5. A method for preparing a repeatable self-healing ramie fiber three-dimensional braided composite material, characterized in that, The method for preparing the repeatable self-healing ramie fiber three-dimensional braided composite material as described in any one of claims 1-4 includes the following steps: Epoxy resin microcapsules and amine curing agent microcapsules were prepared separately. The matrix epoxy resin, matrix curing agent, epoxy resin microcapsules and amine curing agent microcapsules are mixed to obtain a mixture containing microcapsules; Ramie fibers are three-dimensionally woven into fiber preforms; The fiber preform is impregnated with the microcapsule-containing mixture and then cured to obtain a repeatable self-healing ramie fiber three-dimensional woven composite material.

6. The preparation method according to claim 5, characterized in that, The fiber preform is woven using a four-step three-dimensional weaving process.

7. The preparation method according to claim 5, characterized in that, The impregnation of the fiber preform with the microcapsule-containing mixture includes: The microcapsule-containing mixture is injected into the fiber preform under negative pressure using a vacuum-assisted resin transfer molding process.

8. The preparation method according to claim 7, characterized in that, The vacuum negative pressure during the infusion process is 0.06MPa ~ 0.1MPa, and the infusion time is controlled between 30 min and 60 min.

9. The preparation method according to claim 5, characterized in that, The curing process employs a staged heating curing method, comprising a first curing stage, a second curing stage, and a third curing stage performed sequentially. The first curing stage is maintained at a temperature range of 85℃ to 95℃ for 1.5 h to 2.5 h, the second curing stage is maintained at a temperature range of 115℃ to 125℃ for 0.5 h to 1.5 h, and the third curing stage is maintained at a temperature range of 145℃ to 155℃ for 3 h to 5 h.

10. The preparation method according to claim 5, characterized in that, Both the epoxy resin microcapsules and the amine curing agent microcapsules were prepared by in-situ polymerization, which includes: Using epoxy resin or amine curing agent as core material, the core material is added to a base liquid containing urea and formaldehyde and mixed evenly. Then, an emulsifier and a dispersant are added to the base liquid containing the core material and stirred to form an emulsion containing core material droplets. The pH of the emulsion is adjusted to alkaline, so that the urea and formaldehyde undergo a condensation reaction to generate urea-formaldehyde prepolymer; The pH of the emulsion is adjusted to acidic, allowing the urea-formaldehyde prepolymer to polymerize and deposit on the surface of the core material droplets to form a capsule wall. After post-treatment, epoxy resin microcapsules or amine curing agent microcapsules are obtained.